Advances in imaging the neurovascular bundle. - Rai, S; Srivastava, A; Sooriakumaran, P; Tewari, A (2012)
PURPOSE OF REVIEW: Much of the progress in improving potency outcomes after radical prostatectomy has been achieved due to a better visualization of the neurovascular bundle responsible for erectile function. We review the current literature evaluating the existing imaging modalities to image the neurovascular bundle around the prostate pre, intra, and postoperatively, thereby enabling development of surgical techniques for better preservation of nerve function. RECENT FINDINGS: Imaging modalities like multiphoton microscopy, optical coherence tomography, Coherent anti-Raman spectroscopy, exogenous fluoroscopy using prostate-specific membrane antigen, and so on have led to a better appreciation of the neurovascular bundle, thus encouraging novel techniques in nerve preservation during radical prostatectomy. SUMMARY: In an age of heightened patient expectations and increasing life expectancy, better visualization of the neurovascular bundle around the prostate using novel imaging modalities may provide breakthroughs in improving potency outcomes after radical prostatectomy.